2022
DOI: 10.1002/admt.202200259
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Nonlinear Fiber Patterning to Control Tubular Scaffold Mechanical Behavior

Abstract: Melt electrowriting is an additive manufacturing technique capable of fabricating highly biomimetic polymer scaffolds with high‐resolution microarchitecture for a range of tissue engineering applications. The use of a rotating mandrel to fabricate tubular scaffolds using this technique is increasing in popularity; however, the translation of many novel scaffold designs that have been explored on flat collectors has yet to be realized using mandrels. This study reports novel tools to automatically generate scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
(50 reference statements)
1
19
0
Order By: Relevance
“…[25, 43] The hexagonal constructs feature a higher stiffness compared to the rhomboid structures in radial deformation as an effect of their geometry, which is likely the main cause for the linear rise of stress in the recorded measurements and is supported by other studies on the influence of MEW geometries on their mechanical behavior. [44] The rhomboid structures illustrated a certain degree of flexibility depending on the winding angle, allowing the construct to behave elastically in the direction of radial tensile deformation before transitioning to plastic deformation. This allows the rhomboid geometry to assume vastly different mechanical properties depending on the chosen winding angle.…”
Section: Resultsmentioning
confidence: 99%
“…[25, 43] The hexagonal constructs feature a higher stiffness compared to the rhomboid structures in radial deformation as an effect of their geometry, which is likely the main cause for the linear rise of stress in the recorded measurements and is supported by other studies on the influence of MEW geometries on their mechanical behavior. [44] The rhomboid structures illustrated a certain degree of flexibility depending on the winding angle, allowing the construct to behave elastically in the direction of radial tensile deformation before transitioning to plastic deformation. This allows the rhomboid geometry to assume vastly different mechanical properties depending on the chosen winding angle.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, the results here presented showed a match in stress-strain behaviour of native tissue until 10% strain and non-significant differences between native and polymeric grafts for the elastin dominant region, the physiological region, and ultimate tensile strength (UTS). It has been shown that different printing geometries affect stress-strain response of tubular grafts [27], which gives a versatile platform for different engineered tissue. Together, the analysis of the mechanical behaviour here reported show that tuning scaffold geometry the J-shape response and the anisotropy of native vessels were matched.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, within the cardiovascular space, MEW has been utilised to recreate the ECM structure of a heart valve [22] and tubular scaffolds have been fabricated to simulate a patient specific aortic root [24] and heart valve complexes [23]. Furthermore, tubular MEW scaffolds have also been fabricated, demonstrating printability up to 300 stacked layers at a winding angle (WA) of 60° [26], while others having printed auxetic tubular scaffolds and examined the mechanical behaviour of these unique architectures [27]. Very few studies have investigated these tubular scaffolds in the context of tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have worked on different types of strain-limiting layers prior to our work. [26][27][28][29][30] However, there are several limitations. One, these strain-limiting layers are fixed and can hardly alter their length and position.…”
Section: Doi: 101002/aisy202200346mentioning
confidence: 99%